1. The problem statement, all variables and given/known data The question says: f (x)=x2+7x +∫0x(e-tf (x-t)dt. Find f (x). 2. Relevant equations None 3. The attempt at a solution What I did is: Consider the integral: I=∫0x (e-tf (x-t)dt We know that ∫abf (x)dx=∫abf (a+b-x)dc So using it here: 1/ex∫0xetf (t)dt----(1) Leaving the "1/ex part for now. From the original equation f (t)=t2+7t +∫0te-t f (0)dt And we can see that f (0)=0 So f (t)=t2+7t Using (1) without 1/ex.... ∫0xet(t2+7t)dt Which can be calculated to ex(x2+5x -5) Which is when divided by ex becomes x2+5x-5=I Now adding I to the original equation of f (x).. Thus f (x)= 2x2+12x -5x. But in the solution they have done something else. So what is wrong with my solution to this question?